Internal Carotid Injury during Transsphenoidal Resection of Pituitary Macroadenoma Managed with Neurointervention Technique - Sarwar, Mohammad; Tripathy, Laxminarayan; Purkayastha, Sukalyan; Pramanick, Gobinda (Indian Journal of Neurosurgery, 2021)
Iatrogenic internal carotid artery (ICA) injuries during transsphenoidal pituitary tumor surgery are extremely rare but are associated with potentially disabling or life-threatening complications. Management options of ICA injuries are sacrifice, embolization, and endoluminal reconstruction. We report a case of ICA injury during transsphenoidal pituitary macroadenoma surgery, which was managed with endovascular covered stent placement for left carotid-ophthalmic pseudoaneurysm.
Keywords: internal carotid artery injuries; transsphenoidal surgery; pituitary macroadenoma